Rupture Splenic Artery Aneurysm - Afridi, Zia ud Din; Khan, Basharat Ali; Haq, Raja Najam-ul-; Ullah, Sami; Hassan, Azmat; Afridi, Khalid Khan; Shamim, Shumaila (Journal of Postgraduate Medical Institute, 2011)
We present a case of ruptured splenic aneurysm in 18 years old unmarried girl who presented with severe upper abdominal pain and sudden collapse. Ultasound abdomen showed free fluid and ultrasound guided needle aspiration confirmed haemoperitoneum. On laparotomy, a 3cm saccular aneurysm of the middle of the splenic artery was noted. With prompt and urgent management the patients survived.